2014
DOI: 10.5430/jha.v3n6p174
|View full text |Cite
|
Sign up to set email alerts
|

The process of implementing a new working method - a project towards change in a Swedish psychiatric clinic

Abstract: The implementation of evidence-based methods in hospital settings is difficult and complex. The aim of the present study was to highlight the implementation process concerning a new working method, i.e. a new assessment tool, based on the International Classification of Functioning Disability and Health (ICF), among psychiatric nursing staff on five participating wards at a Swedish county hospital. Descriptive, qualitative data were collected through focus group interviews pre-and post-implementation. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…1 and 2 (Johansson, Åstrom, Kauffeldt, Helldin, & Cartström, 2014). A follow-up study based on the qualitative data supported the results of the study (Alverbratt, Carlström, Åström, Kauffeldt, & Berlin, 2014). In the follow-up study, I.W.…”
Section: Methodsmentioning
confidence: 77%
See 4 more Smart Citations
“…1 and 2 (Johansson, Åstrom, Kauffeldt, Helldin, & Cartström, 2014). A follow-up study based on the qualitative data supported the results of the study (Alverbratt, Carlström, Åström, Kauffeldt, & Berlin, 2014). In the follow-up study, I.W.…”
Section: Methodsmentioning
confidence: 77%
“…It was reasonably equal in the distribution of the cultural characteristics. Alverbratt et al (2014) showed that the implementation process of the DLDA was not successful at all in I.W. 1 and I.W.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations